Production and Characterization of Craft Beers with Addition of Campomanesia adamantium O. Berg Fruits and Leave - Verdan, Maria Helena; Santos, Maria do Socorro Mascarenhas; de Castro, Thiago Luis Aguayo; Cardoso, Claudia Andrea Lima (Orbital: The Electronic Journal of Chemistry, 2022)
The increase in the consumption of craft beer is drawing attention to its characteristics. The search for compounds or products that increase stability and guarantee the quality of the beer is fundamental. Here is presented the preparation of two craft beers with the addition of aqueous extract of leaves or fruits of Campomanesia adamantium since this species is known for having a high antioxidant activity. Volatiles compounds and phenolic content, pH, colour and antioxidant action were determined for the samples. The results show that the alcohol content and the number of volatile compounds are on average for most beers. The sample prepared with C. adamantium fruits has a higher content of phenolic compounds and antioxidant potential, compared to the sample added with the aqueous extract of the leaves. Fruits of C. adamantium increased the antioxidant action of craft beers by 79.1%.DOI: http://dx.doi.org/10.17807/orbital.v14i1.1690